2016
DOI: 10.1111/aab.12287
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and behavioural effects of the endophytic Fusarium moniliforme Fe14 towards Meloidogyne graminicola in rice

Abstract: The root‐knot nematode, Meloidogyne graminicola, is an important pest of rice in many rice production areas worldwide. The endophyte Fusarium moniliforme strain Fe14, isolated from a disinfected root of rice, has previously shown potential antagonistic activity against M. graminicola. This study shows the effects of Fe14 on M. graminicola behaviour, infection, development and reproduction. The endophyte Fe14 colonisation significantly reduced M. graminicola penetration into rice roots by 55% and increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Yet, in our study we found a negative effect of the endophyte on the reproduction of M. pygmaeus, and a positive effect on fruit quality and yield, indicating that other mechanisms than changes in nutritional value of the plant are involved as well. Other studies with the Fo162 endophyte showed this fungus may both induce plant defense responses and release various secondary metabolites by itself (Bogner et al, 2017), including indole acetic acid and 4-hydroxybenzoic acid, which may directly or indirectly have affected the survival, reproduction and feeding behavior of M. pygmaeus, similar to what was found for sedetary plant parasitic nematodes (Martinuz et al, 2013;Le et al, 2016).…”
Section: Discussionsupporting
confidence: 55%
“…Yet, in our study we found a negative effect of the endophyte on the reproduction of M. pygmaeus, and a positive effect on fruit quality and yield, indicating that other mechanisms than changes in nutritional value of the plant are involved as well. Other studies with the Fo162 endophyte showed this fungus may both induce plant defense responses and release various secondary metabolites by itself (Bogner et al, 2017), including indole acetic acid and 4-hydroxybenzoic acid, which may directly or indirectly have affected the survival, reproduction and feeding behavior of M. pygmaeus, similar to what was found for sedetary plant parasitic nematodes (Martinuz et al, 2013;Le et al, 2016).…”
Section: Discussionsupporting
confidence: 55%
“…Based on the present research, it is evident that the application of αβ-DC significantly decreased the attractiveness of rice roots to M. graminicola, thus hindered nematode invasion and subsequent infection. Le et al [22] also observed that the root exudates from F. moniliforme Fe14treated plants decreased the attractiveness of M. graminicola to host roots. However, root exudates from Pseudomonas fluorescens-treated plants had no effects on the attractiveness of cyst nematode H. schachtii in sugar beet [28].…”
Section: Discussionmentioning
confidence: 92%
“…After measurement of the toxic effect of this compound on nematodes, further research was conducted to determine the action mode of αβ-DC, with analyses of nematode infectivity, development and attraction behaviour after application of αβ-DC. To date, only a few host-or non-host-specific compounds are known to mediate the attractiveness of crops to nematodes [7,22,28]. Diez and Dusenbery [7] observed that carbon dioxide or amino acids helped RKN M. incognita to trace tomato roots.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the present research, it is evident that the application of αβ-DC significantly decreased the attractiveness of rice roots to M. graminicola, thus hindered nematode invasion and subsequent infection. Le et al [22] observed that the root exudates from F. moniliforme Fe14-treated plants decreased the attractiveness of M. graminicola to host roots. However, root exudates from Pseudomonas fluorescens-treated plants had no effects on the attractiveness of cyst nematode H. schachtii in sugar beet [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation